Problems in the Evaluation of Oxygen Status in Extremely Low Birth Weight Neonates - M. V. Perestoronina; O. V. Korpacheva; S. V. Palyanov; S. V. Nikolayev (Общая реаниматология)
The review summarizes data on a problem with the evaluation of oxygen transport in extremely low birth weight neonates. In particular, it discusses problems with the safety and reliability of methods to monitor the parameters of the body’s oxygen status, with the diagnostic value of some widely available estimates of the degree of respiratory system injury, and with the possibility of their use to predict the duration of ventilatory support and the development of complications and a fatal outcome. Key words: premature infants, extremely low birth weight, respiratory therapy, oxygen status, oxygen gradients.